A Brief Introduction on the Development of Ti-Based Metallic Glasses - Zhang, M.; Song, Y.Q.; Lin, H.J.; Li, Z.; Li, W. (Frontiers in Materials, 2022)
Ti-based metallic glasses (MGs) possess high specific strength, low elastic modulus, high elasticity, high wear and corrosion resistance, and excellent biocompatibility, which make them highly attractive as lightweight high-strength materials as well as biomaterials. However, the glass forming ability (GFA) of Ti-based MGs, particularly those bearing no toxic or noble or heavy metals, i.e. Be, Pd, or Cu alike, largely sets back their wide applications for the restricted critical glass forming size of these Ti-based MGs. In this review, the outlines in developing Ti-based MGs are delineated in order to provide an overall view on the efforts ever made to fabricate bulk-size Ti-based MGs. The state of the art in the knowledge on the GFA of Ti-based MGs is briefly introduced, and possible directions for fabricating bulk size toxic-and-noble-element free Ti-based MGs are discussed.